Levels of phosphorus in the initial development of coffee in soils with different textures - Jesus Souza, Antonio Jackson; Guimarães, Rubens José; Dominghetti, Anderson William; Scalco, Myriane Stella; Colombo, Alberto (Coffee Science - ISSN 1984-3909, 2014)
Aimed to evaluate phosphorus levels in soils with different textures in coffee. We used factor: 4 (phosphorus levels) x 3 (type of soil) in a randomized block with three replications. Evaluated: height, leaf area, leaf, stem diameter, dry mass of shoot, root, and total absolute growth rate, relative growth rate, leaf area index, leaf area ratio and rate of assimilation net. It was found maximum growth of plants dosing 501-720 g P2O5. No effect of high doses of phosphorus (P) to form plants with higher yield potential.